πρίω and πρίων in Aristophanes’ Acharnians, vv. 34–36 - Boris M. Nikolsky (Studia Litterarum)
The article deals with a joke in vv. 34–36 of Aristophanes’ “Acharnians.” Dicaeopolis describes the anguish he feels because of the war and the unwillingness of his fellow citizens to make peace. He longs for his village and his deme and dreams of peace; the city disgusts him. Recalling his former happiness in the village, Dicaeopolis says that his deme unlike the city οὐδεπώποτ’ εἶπεν “ἄνθρακας πρίω”, / οὐκ “ὄξος”, οὐκ “ἔλαιον”, οὐδ’ ᾔδει “πρίω”, / ἀλλ’ αὐτὸς ἔφερε πάντα χὠ πρίων ἀπῆν (34–36). The following interpretation of the joke is argued for. Firstly, the joke is based on the wordplay πρίω / ὁ πρίων. Secondly, πρίω “buy” should be understood not as the shouting of the sellers, but as demands coming from those close to Dicaeopolis or from Dicaeopolis himself. Finally, in the form ὁ πρίων one should see not a proper name or a designation of a saw, but a substantivized participle “gnashing (one’s teeth),” used figuratively to mean “irritated,” “angry.” This participle does not refer to the sellers, but to Dicaeopolis himself and other peasants who are forced to buy goods in the city.